Human Rights in the United Nations Organization - Morgan-Sotomayor, Yanerit (Revista Mexicana de Política Exterior, 2022)
The United Nations (UN) has been fundamental in building a complex scaffolding of legal instruments and international mechanisms to promote and protect human rights. The UN Charter (1945), the establishment of the Human Rights Commission (HRC, 1946) and the Universal Declaration of Human Rights (1948) were the starting points for a system of protection that is being perfected. This essay describes and analyzes this system, particularly through the work of the HRC and in the light of the results of the World Conference on Human Rights (Vienna, 1993), as well as the advances achieved since then. Among other points, the essay highlights the importance of the establishment of the High Commissioner for Human Rights as a means to achieve improved global respect for human rights, and contributions by non-government organizations.